Example of open-source OPS (Open Patent Services) for patent education and information using the computational tool Patent2Net. (September 2016) - Ferraz, Renato Ribeiro Nogueira; Quoniam, Luc; Reymond, David; Maccari, Emerson Antônio
Abstract: This paper discusses the use of Patent2Net, an open source software for extracting and making available information on patents related to dengue fever, a neglected disease of high interest to Brazil. Only ten of 1427 dengue-related patents retrieved in the European worldwide database were filed by Brazilian institutions, showing low contribution of technological research in Brazil regarding this disease. The results enable the creation of new indicators, promoting social responsibility in research, since it is expected that scientific research will produce not only high-impact bibliographic production, but also technological products that can effectively further the search for solutions to problems.